Snapshots of history : portraits of the 21st century pandemic - McCarther, Shirley Marie (American educational history journal ;, 2022)
"This Special Edition of the American Educational History Journal entitled, Snapshots of Educational History: Portraits of the 21st Century Pandemic, is the first special issue in the history of AEHJ. The word, "unprecedented," used literally thousands of times during 2020 on news outlets, in our work environments, and in our daily lives. And indeed, the global pandemic has killed over 600,000 in the United States alone at the time of this writing. The public health crisis shut down everything as we knew it. Captives of sheltering-in-place, scores of incidents displaying horrific police brutality against people of color streamed live on airwaves north, south, east, and west, begetting civil unrest across the country. These are circumstances unlike any we have experienced in our lifetimes. As historians, it is critical that we document this time of crisis so that generations to come can bear witness to this time of turmoil and tragedy. With these ideas in mind, the American Educational History Journal sought to hear from historians and other scholars about this unique and devastating time in our country's history. The Journal honors the traditions of oral history and narrative storytelling as a means to gather the voices of those whose lives have been touched by the COVID-19 crisis, literally everyone around the globe. This special issue deviates a bit from traditional AEHJ requirements in that we specifically invited narratives, not be full-blown historical research studies. The point of this special issue is for authors themselves to serve as the archival material that will benefit future scholars interested in understanding what it meant to live through this health catastrophe while doing the work of educators. We believe we owe it to the historians of the future to share our voices in real time"--